2010
DOI: 10.1155/2010/326507
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds and Tolerance of Physical Pain Among Young Adults Who Self‐Injure

Abstract: Prevalence rates of nonsuicidal self-injury among college students range from 17% to 38%. Research indicates that individuals with borderline personality disorder who self-injure sometimes report an absence of pain during self-injury. Furthermore, self-injury in the absence of pain has been associated with more frequent suicide attempts. The present study examined pain thresholds and tolerance among 44 college students (11 who engaged in self-injury and 33 who did not). Pain thresholds and tolerance were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…All of the studies PAIN AND SELF-HARM: A SYSTEMATIC REVIEW 15 that assessed pain threshold found that the NSSI group demonstrated a significantly higher pain threshold than healthy matched controls. McCoy et al (2010) found the NSSI group to have a higher pain threshold than controls on the first trial, but did not find a significant difference between groups on the two subsequent threshold trials or between the mean thresholds of the two groups; potentially suggesting that multiple trials result in habituation.…”
Section: Strengths and Limitations Of The Evidence For Altered Pain Tmentioning
confidence: 74%
See 3 more Smart Citations
“…All of the studies PAIN AND SELF-HARM: A SYSTEMATIC REVIEW 15 that assessed pain threshold found that the NSSI group demonstrated a significantly higher pain threshold than healthy matched controls. McCoy et al (2010) found the NSSI group to have a higher pain threshold than controls on the first trial, but did not find a significant difference between groups on the two subsequent threshold trials or between the mean thresholds of the two groups; potentially suggesting that multiple trials result in habituation.…”
Section: Strengths and Limitations Of The Evidence For Altered Pain Tmentioning
confidence: 74%
“…As several studies have demonstrated altered pain threshold and tolerance in community samples (e.g. Gratz et al, 2011;McCoy et al, 2010;Hooley et al, 2010), the observed differences are unlikely to be the result of either of these explanations. Much more likely is the third explanation they present, that of habituation via endogenous opioid mechanisms of analgesia.…”
Section: Candidate Explanatory Mechanismsmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, in some circumstances, the tolerance to pain of a person can change after a stressful experience (e.g., death of a loved one, self-injury). In a study by McCoy et al, 46 it was found that participants with previous experience of self-injury had a significantly higher pain tolerance but the same pain threshold compared to normal controls; it was hypothesized that selfinjury increases the desensitization to fear and pain.…”
Section: Pain Assessmentmentioning
confidence: 99%